2022
DOI: 10.1242/jcs.260059
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of cytosolic tails in the Jen1 carboxylate transporter are critical for trafficking and transport activity

Abstract: Plasma membrane (PM) transporters of the major facilitator superfamily (MFS) are essential for cell metabolism, growth and response to stress or drugs. In Saccharomyces cerevisiae, Jen1 is a monocarboxylate/H+ symporter that provides a model to dissect the molecular details underlying cellular expression, transport mechanism and turnover of MFS transporters. Here, we present evidence revealing novel roles of the cytosolic N- and C- termini of Jen1 in its biogenesis, PM stability and transport activity, using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Considering that three α-arrestins mediate the internalization of Ste2 and Ste3 ( i.e., Rod1, Rog3 and Art1 or Aly1, Aly2 and Art1, respectively), there is opportunity for both a common regulatory sequence ( i.e., for Art1) and divergent regulatory sequences ( i.e., for Rod1/Rog3 vs Aly1/Aly2) in Ste2 and Ste3. To date, only a few α-arrestin interaction interfaces have been defined for any membrane protein, but based on these that are defined it appears that α-arrestins preferentially associate with acidic patches on cargo proteins (Lin et al ., 2008; Wawrzycka et al ., 2019; Ivashov et al ., 2020; Barata-Antunes et al ., 2022). Our earlier work demonstrated that α-arrestins can bind the C-tails of Ste3 and Ste2, suggesting that key interactions needed to recruit α-arrestins occur in these regions (Alvaro et al ., 2014; Prosser et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that three α-arrestins mediate the internalization of Ste2 and Ste3 ( i.e., Rod1, Rog3 and Art1 or Aly1, Aly2 and Art1, respectively), there is opportunity for both a common regulatory sequence ( i.e., for Art1) and divergent regulatory sequences ( i.e., for Rod1/Rog3 vs Aly1/Aly2) in Ste2 and Ste3. To date, only a few α-arrestin interaction interfaces have been defined for any membrane protein, but based on these that are defined it appears that α-arrestins preferentially associate with acidic patches on cargo proteins (Lin et al ., 2008; Wawrzycka et al ., 2019; Ivashov et al ., 2020; Barata-Antunes et al ., 2022). Our earlier work demonstrated that α-arrestins can bind the C-tails of Ste3 and Ste2, suggesting that key interactions needed to recruit α-arrestins occur in these regions (Alvaro et al ., 2014; Prosser et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Jen1 was also reported to transport selenite [12] and it is expressed and localized at the PM when cells are growing on non-fermentable carbon sources, including lactate, pyruvate, acetate and ethanol [13]. A variety of signals induce Jen1 internalization and degradation, including glucose [10,[14][15][16][17][18][19][20], rapamycin, and cycloheximide ( [21], see also [5] for a review). In our recent study [21],…”
Section: Introductionmentioning
confidence: 99%